Clinical outcomes of an olive wire and external fixator versus a metallic screw in the treatment of inferior tibiofibular syndesmosis injuries in ankle fractures. Issue 3 (April 2023) - Jin-tao, Qu; Mei, Wang; Chao-jun, Li; Zi-tian, Wang; Guang, Peng; Hao, Yang; Yu-quan, Jiang; Yu, Tang
Abstract: Background: Metal screws are the most widely used in treating syndesmotic injuries, but failure and the rigidity of the screws can threaten the success of the treatment and increase the cost of care. We have provided an alternative with an olive wire and external fixator(OWEF) used for syndesmotic fixation. Methods: A retrospective longitudinal follow-up study was conducted. From February 2011 to January 2018, 58 of 72 patients with ankle fractures and associated syndesmotic disruption were treated with either screw or OWEF fixation. The costs, complications, and clinical outcomes using Olerud-Molander score and Visual Analog score in screw and OWEF fixation group were compared. Results: We found the severity of the injury, BMI of the patients and the different fixation methods were determinants of the complications and clinical outcomes. But if no malreduction of the syndesmosis was present, no difference in clinical result was detected. Conclusion: The OWEF method appeared to be at least equally functional and effective to screw fixation while maintaining possible lower complication rate. Levels of clinical evidence: Level 3